Educational Perspectives in Modern and Simple Society - Faris Abdurrahman; Firman; Riska Ahmad (Yayasan Citra Dharma Cindekia, 2022)
Education is the door to the modern world, because only through education can socio-cultural changes be carried out, namely developing knowledge, adjusting values and attitudes that support development and mastering various skills in using advanced technology to accelerate the development process. The process of developing all aspects of life is called modernization.One very big difference between education in simple societies and modern societies is the shift away from the need for an individual to learn something on which everyone agrees. Children of the common people went to an expert in their tribe to learn what could be learned about certain activities such as fishing, hunting and setting traps. Modern society educational institutions have a series of supporting indicators that are modern, while in a simple society the form is different, the method of application may be different and the equipment is also different. The direction of socio-cultural change, modernization, or development that a society undergoes in science and technology helps people solve almost all of the problems they face in order to achieve the level of welfare or prosperity that they desire, is the direction that all nations around the world will aim for.